2020
DOI: 10.6000/2292-2598.2020.08.03.32
|View full text |Cite
|
Sign up to set email alerts
|

Professional Self-Realization as a Factor in the Psychological Well-Being of Specialists of Caring Professions

Abstract: Research Objective: the article discusses the mutual influence of professional self-realization and the psychological well-being of specialists of caring professions. Methodology: correlation and comparative analysis in different professional groups of specialists. The study involved 465 volunteers with work experience of 3 to 40 years: teachers, doctors, medical personnel, psychologists of state and private enterprises. Several standardized self-reports were used to collect data: Ryff's Scales of Psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 15 publications
(16 reference statements)
0
3
0
8
Order By: Relevance
“…Job satisfaction is usually associated with professional success and loyalty to the employer organization. This connection has been confirmed by numerous theoretical models and empirical studies (Kumari, 2011;Dik et al, 2013;Glavinska et al, 2020). It is logical to expect that a person with a high level of satisfaction will be more involved and interested in the results of his job performance, share corporate goals and the values of the corporate culture.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Job satisfaction is usually associated with professional success and loyalty to the employer organization. This connection has been confirmed by numerous theoretical models and empirical studies (Kumari, 2011;Dik et al, 2013;Glavinska et al, 2020). It is logical to expect that a person with a high level of satisfaction will be more involved and interested in the results of his job performance, share corporate goals and the values of the corporate culture.…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies, which have accumulated data on job satisfaction in different occupational samples (medical staff, teachers, psychologists, managers, private entrepreneurs, etc. ), have shown that parameters of some JSQ scales and the overall index of satisfaction vary depending on working conditions or organizational space in which activities are carried out (Glavinska et al, 2020), as well as according to job title (Gura & Veldbrecht, 2021). This contribution has allowed specifying these differences and using them as a basis for planning psychological interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main features of socionomy specialists include value orientations, interpersonal communication and emotional regulation skills, conflict avoidance skills, moral and volitional qualities, tolerance, creativity (Pankevich, 2018). Professional self-development and the resulting professional self-fulfilment of specialists evidence their competence, self-acceptance and psychological wellbeing (Glavinska et al, 2020). The importance of motivating socionomy specialists to build a successful professional career, gaining practical experience based on self-development is noted (Spivak et.…”
Section: Literature Reviewmentioning
confidence: 99%